Livogena: The Ikteros Curse-A Jaundice Narrative Card and Board Game for Medical Students - Krishna Mohan Surapaneni (Association of American Medical Colleges, 2024)
Introduction Jaundice is a common condition that requires integrating knowledge of biochemistry, physiology, pathology, and general medicine. However, medical students face difficulty in learning with passive teaching methods. To enhance their learning, an educational story game that promotes active learning and assessment with immediate feedback was implemented. Methods This jaundice game was named Livogena: The Ikteros Curse-denoting the liver as the principal organ and jaundice (icterus) as a problem. One hundred fifty first-year medical students were divided into small groups to play using a game board and cards. The players moved ahead on the game board by providing the correct answer and completing the activities. The first team to reach the end was the winner. Perceptions and feedback questionnaires were distributed to students at the end of the game. Individual views about the game were recorded for qualitative analysis. Also, to analyze the effectiveness of this intervention, pre- and posttests on jaundice were conducted. Results Livogena: The Ikteros Curse resulted in a highly significant improvement in students' knowledge and application skills in jaundice, from 5.5 (SD = 2.4) in the pretest to 11.2 (SD = 7.6) in the posttest for 20 marks (p < .001). Students perceived and rated the game exceptionally positively. Discussion This educational game significantly increased learners' understanding of the concepts of jaundice. Highly positive perceptions from students further affirm this to be a creative innovation to enhance their learning and application of knowledge in an active and team-based learning environment.